2023
DOI: 10.3389/fpls.2022.1096800
|View full text |Cite
|
Sign up to set email alerts
|

β-D-XYLOSIDASE 4 modulates systemic immune signaling in Arabidopsis thaliana

Abstract: Pectin- and hemicellulose-associated structures of plant cell walls participate in defense responses against pathogens of different parasitic lifestyles. The resulting immune responses incorporate phytohormone signaling components associated with salicylic acid (SA) and jasmonic acid (JA). SA plays a pivotal role in systemic acquired resistance (SAR), a form of induced resistance that - after a local immune stimulus - confers long-lasting, systemic protection against a broad range of biotrophic invaders. β-D-X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The expression level of the predicted genes Glyma.08G074600, Glyma.08G074700, and Glyma.12G043600 were appreciably upregulated in the resistant accession compared to the susceptible accession on the 7th day, which implies a possibility of its involvement in soybean's reaction to C. ilicicola resistance. For instance, the Glyma.08G074700 homolog in Arabidopsis, AT5G64570, encodes a secreted beta-d-xylosidase that enhances resistance to Botrytis cinerea [60] as well as boosts signaling related to systemic immunity in Arabidopsis thaliana [61].…”
Section: Marker-trait Associations (Mtas) Haplotype Analysis and Cand...mentioning
confidence: 99%
“…The expression level of the predicted genes Glyma.08G074600, Glyma.08G074700, and Glyma.12G043600 were appreciably upregulated in the resistant accession compared to the susceptible accession on the 7th day, which implies a possibility of its involvement in soybean's reaction to C. ilicicola resistance. For instance, the Glyma.08G074700 homolog in Arabidopsis, AT5G64570, encodes a secreted beta-d-xylosidase that enhances resistance to Botrytis cinerea [60] as well as boosts signaling related to systemic immunity in Arabidopsis thaliana [61].…”
Section: Marker-trait Associations (Mtas) Haplotype Analysis and Cand...mentioning
confidence: 99%
“…Furthermore, xylose has emerged as a prominently investigated sugar in plant disease contexts. Studies have showcased its potential to enhance the management of cucumber wilt disease ( Xu et al, 2019 ) and bolster colonization by the plant growth-promoting rhizobacterium B. velezensis , thereby mitigating wilt symptoms ( Bauer et al, 2023 ). Intriguingly, xylose was also found to have contrasting effects, serving both as a nutrient and a virulence enhancer for X. citri ( Alexandrino et al, 2023 ).…”
Section: Sugar Manipulation As a Strategy For Plant Disease Managementmentioning
confidence: 99%
“…SA as a hormone plays a critical role in the regulation of a multitude of physiological processes such as seed germination, vegetative growth, photosynthesis, respiration, thermogenesis, flower formation, seed production, responding to pathogens, and stimulating plant defense immunity (Lastochkina et al, 2020 ; Ansari et al, 2021 ). Under biotic stress conditions, SA fulfills a key function as an endogenous signal mediating local defense responses (Bauer et al, 2022 ; Zhang et al, 2023 ). In fungi, it has been found that high temperatures could increase the SA content in the extracellular fluid of Pleurotus ostreatus (Qiu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%